(untitled) (De la Crítica, 2025)
Language anxiety in adult English as a Foreign Language (EFL) learners during group conversations is a complex process where motivation, cognitive strategies, and socio-affective factors collectively influence success. To comprehensively explore this topic, this essay undertook a documentary investigation, aiming for a broad understanding, by identifying influential factors, and potential didactic strategies to mitigate the impact of anxiety and foster a safer, more effective learning environment. Ultimately, this work suggests that by thoroughly understanding the manifestations of language anxiety and implementing effective pedagogical strategies, learners’ experiences and academic performance can be significantly improved.